2009
DOI: 10.1123/ijsc.2.3.274
|View full text |Cite
|
Sign up to set email alerts
|

SportsCentral as Winner or Loser? Centralcasting as Strategy for Efficient Local Sportscast Production

Abstract: The amount of time dedicated to sports coverage in local news has decreased substantially in recent years. In fact, some networks have eliminated traditional sports segments or outsourced them to national organizations. The now defunct Sinclair Broadcast Group’s SportsCentral represented a cost-efficient way to produce local sports segments in multiple media markets, and this study sought to understand how SportsCentral broadcasts compared with traditional broadcasts in 3 markets. An analysis of SportsCentral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The study found statistically significant differences between remotely delivered (News-Central) and locally produced newscasts on story location, with local newscasts carrying significantly more local stories and significantly fewer national/international stories. Mills and Daniels (2009) examined Sinclair's SportsCentral sportscasts and found they carried significantly fewer local stories than local station sportscasts within the same markets. Yet Sinclair's is not the only foray into remote delivery of local TV news.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found statistically significant differences between remotely delivered (News-Central) and locally produced newscasts on story location, with local newscasts carrying significantly more local stories and significantly fewer national/international stories. Mills and Daniels (2009) examined Sinclair's SportsCentral sportscasts and found they carried significantly fewer local stories than local station sportscasts within the same markets. Yet Sinclair's is not the only foray into remote delivery of local TV news.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The first study (2007) detailed such incidents as the same remotely delivered newscast airing for hours on end, as well as remote newscasts emphasizing conflict stories over a major local celebration and missing major local stories such as a nearby forest fire. The second study (2010) included a content analysis of locally and remotely produced newscasts, with findings similar to Daniels (2008) and Mills and Daniels (2009): Many more local stories on locally produced newscasts, many more national and international stories on remotely produced programs. I later interviewed news workers involved with outsourcing, who described the challenges of producing newscasts for communities with which they were unfamiliar or had never visited (Hood, 2011).…”
Section: Introductionmentioning
confidence: 99%